2006
DOI: 10.1051/0004-6361:20053203
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia cores in high mass star formation regions

Abstract: We observed a sample of 35 water masers not coincident with known HII regions and/or low mass young stellar objects (YSOs) with the Effelsberg 100 m telescope in the NH 3 (J, K) = (1, 1), (2, 2), (3, 3) and (4, 4) transitions. Sixteen sources were detected in the NH 3 emission. The detection rate is 46%. All these sixteen sources have NH 3 (1, 1) and (2, 2) emission, among which four sources have NH 3 (3, 3) emission. Comparing with the IRAS and the 2MASS data, we analyzed the relationship between the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 35 publications
12
67
1
Order By: Relevance
“…13. A correlation between T K and L bol was also found by e.g., Churchwell et al (1990), Wu et al (2006), Urquhart et al (2011), and by Sánchez-Monge et al (2013b), for cores in clustered environments, using the luminosity of the whole region.…”
Section: Temperaturessupporting
confidence: 70%
“…13. A correlation between T K and L bol was also found by e.g., Churchwell et al (1990), Wu et al (2006), Urquhart et al (2011), and by Sánchez-Monge et al (2013b), for cores in clustered environments, using the luminosity of the whole region.…”
Section: Temperaturessupporting
confidence: 70%
“…Previous observations of NH 3 (Wouterloot et al 1988;Myers et al 1991;Harju et al 1993;Ladd et al 1994;Molinari et al 1996;Jijina et al 1999;Wu et al 2006;Urquhart et al 2011Urquhart et al , 2015, C 18 O (Saito et al 2001;Ridge et al 2003;Maud et al 2015), and 13 CO (Wang et al 2009;Lundquist et al 2015) suggest that the line width is correlated with luminosity, which indicates the presence of a link between formed stars and velocity dispersion. We investigate the line width-luminosity relation in the case of the dense gas tracer H 2 CO. We plot the line width-luminosity relation in Figure 9.…”
Section: Line Width-luminosity Relationmentioning
confidence: 90%
“…Towards C5, dense molecular tracers such as CS (Beuther et al 2002) and NH 3 (Wu et al 2006) have been observed. The signature of high-velocity CO gas (Yang et al 2002) has also been reported towards C5.…”
Section: Nature Of Sources Within Ir Blobs And/or Clumpsmentioning
confidence: 99%